An analysis of pronunciation errors in English of six UTAR Chinese Studies undergraduates - Kho, Ivy Chiann Yiing (2011)
The construction of gender in terms of masculinity and femininity in The Good Earth by Pearl S. Buck is examined based on the social constructionist theory. Wang Lung’s masculinity and Olan’s femininity are social constructs which are shaped by Confucian culture. The portrayal of both characters is also influenced by the author’s background. The qualitative methods used in this study include close reading, thematic analysis and biographical analysis. To begin with, Wang Lung’s masculinity is molded by his father and Confucian culture. Feudalism also influences his appreciation of sons, concubines and bound feet. Similarly, Confucianism and feudal norms construct O-lan’s femininity. Her parents and the mistress of the House of Hwang shape her beliefs of women’s responsibilities in a Confucian culture. Furthermore, Wang Lung and O-lan are depicted based on the author’s parents. Buck’s father was oppressive while Buck’s mother was submissive. This study is carried out as there seems to be relatively little research which employed the social constructionist theory to examine gender in The Good Earth. For further research, this theory can be used to study the element of superstition. On the whole, Wang Lung’s masculinity and O-lan’s femininity result from the Confucian culture instead of biological sources.